2012
DOI: 10.4103/0257-7941.103180
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antidiabetic, antioxidant effect and safety profile of gomutra ark in Wistar albino rats

Abstract: The effect of Gomutra ark (GoA) on experimental alloxan-induced diabetes in rats was studied. For this purpose, Wistar albino rats of either sex weighing 200-250 g were used. The biochemical parameters like blood sugar, vitamin C, and malondialdehyde release were measured. The safety profile of GoA was evaluated using acute and chronic toxicity studies. GoA significantly lowers blood glucose in diabetic rats although the observed effect was found to be less than glibenclamide. It significantly lowers the level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…The wound healing activity of cow urine ark in diabetic Wistar albino rats was evaluated in this study using several models based on previous research, which demonstrated significant anti-diabetic, antimicrobial, and antioxidant effects [ 11 , 12 , 22 ]. Besides, volatile fatty acids present in cow urine ark probably contribute to its antioxidant properties which might reduce oxidative stress in diabetic wounds [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The wound healing activity of cow urine ark in diabetic Wistar albino rats was evaluated in this study using several models based on previous research, which demonstrated significant anti-diabetic, antimicrobial, and antioxidant effects [ 11 , 12 , 22 ]. Besides, volatile fatty acids present in cow urine ark probably contribute to its antioxidant properties which might reduce oxidative stress in diabetic wounds [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Medicinal properties of cow urine such as bioenhancer, antibiotic, antifungal, and anticancer have been patented under US patent number 6,896,907 and 6,410,059 [ 9 , 10 ]. Several studies had suggested that cow urine has anti-diabetic potential probably due to its antioxidant properties [ 11 , 12 ]. Besides, external application of cow urine on excision wound (EW) has shown to hasten the wound healing [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the potent ABTS reduction observed in this assay might be due to the antioxidant compounds present in cow urine. Sachdev et al ( 2012 ) revealed that cow urine contains volatile fatty acids such as acetic acid 2 propenyl ester, acetic acid methyl ester, 2,2,3,trichloro propionic acid, butanoic acid-3methyl, propyl ester, 1 H indol-3-acetate, acetic acid phenyl ester and quinoline that may act as an antioxidants. This has been confirmed by the estimation of thiobarbituric acid, ascorbic acid, DPPH radical scavenging activity and ABTS assay.…”
Section: Discussionmentioning
confidence: 99%
“…The phenolic compounds and flavonoid constituents in lupin seed extracts have important antioxidant activity [ 51 , 52 ]. Lupin protein hydrolysates present anti-inflammatory properties [ 53 ]. The antifungal and antibacterial activities have been demonstrated in different studies that report an inhibitory effect toward various bacterial and fungal pathogens [ 54 , 55 ].…”
Section: Lupin a Unique Legume In So Many Waysmentioning
confidence: 99%